Awareness of diabetes mellitus among public attending the primary health centers in Malaysia - Humaira, Abdul Latif; Mohd Rashid, Ab Hamid; Noor Azlinda, Zainal Abidin (Universiti Kebangsaan Malaysia, 2018)
Diabetes is a steadily growing problem in Malaysia and the increase of diabetics’ patients in Malaysia is worrisome. In relation to this, the purpose of this study is to test Diabetes Mellitus Awareness Model (DMAM) consisting of five constructs, namely knowledge, attitude, environment, symptom and diabetics awareness. This study develops the conceptual model for studying the factors among public in Malaysia in order to possibly increase the awareness towards the ailment. A total of ten hypotheses have been proposed to test the relationship in the hypothesised model between the five constructs under study. Structural equation modelling (SEM) with SmartPLS software using Partial Least Squares estimation (PLS) is used for modelling analysis. The study was conducted in two health clinics, namely Klinik Kesihatan Paya Besar and Klinik Kesihatan Padang Rumbia from 1 September 2015 to 15 October 2015. A total of 550 questionnaires were distributed and 523 questionnaires were successfully collected. From the results, it shows that knowledge on diabetics has a significant impact on a) environment, b) attitude and c) awareness towards diabetics. Next, the environment significantly influences the attitude, and attitude has a significant influence on the awareness. However, the results also show that there is no significant relationship between the environment towards awareness. In addition, both knowledge and environment has no significant effect towards symptoms of diabetes mellitus ailment. The finding also shows that the causal relationship of attitude on symptoms, and the relationship between symptom and awareness are not significant. In conclusion, the healthcare authorities may refer to DMAM as a basis model for increasing the awareness regarding this ailment especially among the public.